2008
DOI: 10.1089/apc.2008.0022
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Patterns of Alcohol and Drug Use among HIV-Infected Patients in the United States Southeast

Abstract: Alcohol and drug use are common among HIV-infected patients and are important determinants of secondary transmission risk and medication adherence. As part of the Coping with HIV/AIDS in the Southeast (CHASE) Study, 611 HIV-infected patients were consecutively recruited from eight clinical care sites in five southeastern U.S. states in 2001-2002. We examined the distribution and predictors of alcohol and drug use in this sample with an emphasis on psychosocial predictors of use. In the prior 9 months, 27% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 48 publications
9
86
2
1
Order By: Relevance
“…Higher frequency of alcohol consumption induces a stronger maladaptive coping strategy among HIV-positive people because the alcohol may be associated with other behavioral disorders that lead to non-adherence to ART [13]. Alcohol users may also be less likely to seek support from their family, friends, and caregivers, which may lead to non-adherence to ART [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher frequency of alcohol consumption induces a stronger maladaptive coping strategy among HIV-positive people because the alcohol may be associated with other behavioral disorders that lead to non-adherence to ART [13]. Alcohol users may also be less likely to seek support from their family, friends, and caregivers, which may lead to non-adherence to ART [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HIV-positive people who use alcohol frequently can experience more conflict with their partners, which can impact negatively on spousal support and lead to poor compliance with ART [12]. Harmful alcohol drinking can also reduce coping skills and increase the likelihood of opportunistic infections [13]. Moreover, HIV-positive people who used illicit substances also had alcohol-use disorders resulting in non-adherence to ART [14].…”
Section: Introductionmentioning
confidence: 99%
“…As with Tables 1 and 2, when at least two studies reported results based on the same dataset, only summaries are shown for the study that provided the most detail. Summaries for the following eight studies are therefore not listed in Table 3: Cooper et al [69][70][71], Gillen [72], Gore-Felton et al [73], Gow et al [74], Pence et al [75], and Piazza-Waggoner et al [76]. Compared to the studies that had conducted their own exploratory factor analyses, those that based their factor structure on previous research tended to have smaller samples sizes.…”
Section: Studies That Did Not Conduct Their Own Exploratory Factor Anmentioning
confidence: 99%
“…Religious well-being is positively related to self-efficacy to use condoms [42], and religious coping is associated with reduced likelihood of recent unprotected sex among men but not women [47]. Religious coping and attendance at religious services in particular have been negatively related to substance use, including use of alcohol, crack cocaine, and other non-marijuana substances [7,48]. In a similar vein, a study of congestive heart failure patients found that spiritual support and positive religious coping were related to less substance use [44].…”
Section: Religious Coping and Active Copingmentioning
confidence: 99%